Strategy and Behaviors in the Digital Economy - Orlando, Beatrice (IntechOpen, 2020)
Strategy and Behaviors in the Digital Economy is a collection of reviewed and relevant research chapters, offering a comprehensive overview of recent developments in the field of Business, Management and Economics. The book comprises single chapters authored by various researchers and edited by an expert active in this research area. All chapters are complete in itself but united under a common research study topic. This publication aims at providing a thorough overview of the latest research efforts by international authors on this field of study, and open new possible research paths for further novel developments.